Informativity of Locally Estimated Odd-Numbered Higher Fatty Acids for Differential Diagnosis of HSIL and Cervical Cancer - E. V. Kayukova; T. E. Belokrinitskaya; A. M. Ziganshin; V. A. Mudrov (Креативная хирургия и онкология, 2022)
Background. Current issues in the cytological assessment of cervical epithelium can hamper differential diagnosis of high-grade squamous intraepithelial lesion (HSIL) and cervical cancer.Aim. To determine the informativity of locally estimated values of odd-numbered higher fatty acids as differential markers in HSIL and cervical cancer.Materials and methods. Previous original data on the higher fatty acids content in cervical biopsy of primary pre-treatment HSIL and cervical cancer patients were analysed retrospectively. The study cohorts: clinical cohort I — 30 HSIL patients; clinical cohort II — 45 primary stage I squamous cervical cancer patients. Statistical methods included the analyses of ROC curves, sensitivity (Se), specificity (Sp) and accuracy (Ac).Results. Among all odd-numbered higher fatty acids, the following molecular markers (local thresholds) are differential for cervical cancer: C15:0 ≤1.91 %/cell (Se = 0.81; Sp = 0.84; Ac = 0.83; AUC = 0.81); C15:1 ≤1.72 %/cell (Se = 0.96; Sp = 0.91; Ac = 0.92; AUC = 0.96); C17:0 ≤2.95 %/cell (Se = 0.94; Sp = 0.93; Ac = 0.97; AUC = 0.97); C17:1 ≤1.11 %/cell (Se = 0.96; Sp = 0.98; Ac = 0.96; AUC = 1.0); C19:0 ≤1.17 %/cell (Se = 1.0; Sp = 1.0; Ac = 1.0; AUC = 1.0).Discussion. Tumour cells are known to possess atypical metabolism, which produces large amounts of higher fatty acids with odd numbers of carbon atoms. The study focused on the value of locally estimated odd-numbered higher fatty acids as differential molecular markers in HSIL and cervical cancer.Conclusion. The results suggest that C19:0 estimates are applicable in diagnosis of HSIL and cervical cancer.